The problems of interaction between the state and the Muslim community: the case of the Republic of Bashkortostan - A. T. Berdin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The author explores the dynamics of the historical and socio-cultural cooperation between the state and the Muslim community in the Republic of Bashkortostan, criticizes some historiographical stereotypes, in particular, the exaggeration of the role of Bulgar in islamization of the region. The author examines the basic moments of conflict within the Ummah Bashkiria, structurally marks its main actors, including Sufi tar-iqahs and Wahhabi jamaat. The author discloses the nature of the interaction between national and ethno-religious movement of Bashkir youth. The author determines the cause of the spread of Salafism among young people, shows the similarities and differences in the motives of neophytes in comparison with other «Muslim» republics of Russia.